The Reality of the Awareness of the Workers in the National Health Information Center of the Importance of Big Data: A Survey Study - Selmi, Amani Abdul Qawi Obaid Al; Alqarni, Abdulrahman Obaid Ali (Communications in Mathematics and Applications, 2022)
This study aimed at identifying the reality of the awareness of workers in the National Health Information Center of the importance of big data. It used the descriptive approach (survey study) through the personal interview tool with the aim of collecting data to identify the views of the study sample about the main question of the study, which is “What is the reality of workers’ perceptions in the National Health Information Center of the importance of big data?”From this main question the following sub-questions derive: First, “What is the awareness of workers at all administrative levels of the concept and importance of managing and analyzing big data?”. Second, “What is the importance of managing big data in the National Health Information Center?”. Third, “What value does managing big data add to the National Health Information Center?”. Out of This third question, emerge the following sub-questions: First, “What is the value of big data in the National Health Information Center follow-up on e-health projects?”. Second, “What is the value of big data in decision support for health policy-making?”. Third, “What value does big data add to support health innovation?”. Fourth, “What value does big data add to enhance clinical trials?”. Fifth, “What is the investment value of big data?” The study community consisted of the National Health Information Center, and the study sample was the intentional sample, which consisted of officials, administrative and technical staff directly related to dealing with big data in the center. In its results, the study found a difference in the awareness of the workers in the center of the importance of big data, according to the administrative levels they occupy. The strategic position of the center and its role in making health decisions at the national level and the huge volumes of data it contains and produces illustrate the importance of managing big data in the center. The value added by the management of big data in the center is namely assistance in following up on e-health projects, assisting decision-makers in making health policies. In addition, it is considered one of the most important tributaries to support the process of health innovation and health research, to enhance the aspect of clinical trials, and in investment. In light of these results, the study recommended raising awareness among the center employees through holding seminars and specialized workshops, directing the health sectors and relevant authorities and guiding them with the basic rules for managing and preserving big data, completion of operational plans to actually launch the investment phase of big data
Keywords: Big Data; Big Data Management; The National Health Information Center